Kaitan Pendidikan dan Kepribadian Manusia dalam Mencapai Tujuan Pendidikan Nasional - Ni Nengah Selasih (Jurnal Penjaminan Mutu, 2016)
Human nature, in terms of education, according Lengeveld is educabile animal, namely being able to be educated; educandum animal, the creature must be educated; education homo, that being on the side can and should be educated can and should educate. The role of education in fostering personality summed up in the goals of education derived or determined by the principle of ontological view and axiologis. Man is the subject, as well as objects of education. Cultured adult human is the subject of education in the sense of responsible education. Human undertaking to foster the commuity, preserve the natural environment together, primarily responsible for the dignity of humanity. Based on the analysis of the structure of the human soul and personality, the human behavior is determined by the source and the id, ego, and superego. Therefore, compulsory education is deepened to better understand of human behavior or character. In particular, for educational purposes, to understand human nature, personality, means to understand individual interests, aspirations, potentials, and personal identity, and are fundamental to the effectiveness of the educatonal process, an obligation also to respect the dignity, personality, and uniqueness of a person in order to self-realization. Science of life for science education is a very valueble complementation. Pedagogic without the same life science with practice without theory. Education without understanding the human means to build something without knowing for what, how, and why people are educated. Without an understanding of the people, the unique nature of the individual, and the potential that it will be fostered, then education would be misdirected. Even without the good sense, then education would rape human nature.